French administration and the european union / by translated by Anne and Handley Stevens - "Sauron,Jean-Luc" (Paris, 2000)
This book explains how the EU institutions are organised and how they operate. It describes how the structures and working methods of the French government have been adapted to respond to the demands of EU membership. Topics discussed include interministerial co-ordination, the involvement of the national Parliament in the negotiations leading up to EU legislation, the transposi tion of EU directives into national law, the application of EU law by the national courts, and the training of officials in EU affairs.
Keywords: European Union-Law